Application of effective theory and Grassmann variables to model compact binaries with spin - Mautner, G [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We review how an approximation of the potential between two spin-less bodies is calculated, up to second order in the velocities, by employing eﬀective ﬁeld theory methods to model their interaction though the gravitational ﬁeld. By extending this methodology to take into account their spin degrees of free domand by describing such spin degrees of freedom in terms of Grassmannian variables, we calculate the additional terms in the potential due to spin-spin and spin-orbital interactions. Finally, we calculate the energy as a function of rotational frequency of a binary system, including the eﬀect of these spin related terms. Such results are becoming increasingly relevant in possible measurements by gravitational observatories like LIGO [1] or VIRGO [2]

Começamos por revisar um modo de calcular a energia potencial entre dois corpos sem spin até segunda ordem nas velocidades, através da aplicação de uma Teoria de Campos Efetiva que modela a interação entre eles por meio do campo gravitacional. Estendendo este método para que leve em conta também os graus de liberdade de spin, e descrevendo tais graus de liberdade através de variáveis de Grassmann, calculamos termos adicionais no potencial advindos das interações spin-spin e spin-orbital. Finalmente, calculamos a energia como função da frequência de rotação do sistema binário, incluindo o efeito destes termos relacionados a spin. Tais resultados devem tornar-se cada vez mais relevantes para possíveis medições em observatórios de ondas gravitacionais tais como LIGO [1] e VIRGO [2]
Keywords: Supersimetria; Teoria de campos (Física); Sistema binario (Matematica)